2020
DOI: 10.1016/j.pec.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness in Egypt about COVID-19 spread in the early phase of the pandemic

Abstract: Highlights Egypt is a tourist and investment country. Public awareness of the coronavirus can oppose disease. Participants had good knowledge of coronavirus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 10 publications
2
35
0
Order By: Relevance
“…This might be because of the serious situation of the epidemic and the overwhelming news reports on this public health emergency and that the government and some organizations like WHO have made their best effort to make communities knowledgeable about the coronavirus pandemic state. These study findings were supported by findings of (Elgendy, El-Gendy et al 2020) in their study "Public awareness in Egypt about COVID-19 spread in the early phase of the pandemic", where nearly 82% of the respondents were classified as knowledgeable about coronavirus and its treatment. Also, in the same line, (Narayana, Pradeepkumar et al 2020) in their study titled "Knowledge, perceptions, and practices towards COVID-19 pandemic among the general public of India: A cross-sectional online survey", found that the respondents' mean knowledge score of COVID-19 was 7.47, indicating that the overall accurate knowledge rate was 74.7%.…”
Section: Discussionsupporting
confidence: 74%
“…This might be because of the serious situation of the epidemic and the overwhelming news reports on this public health emergency and that the government and some organizations like WHO have made their best effort to make communities knowledgeable about the coronavirus pandemic state. These study findings were supported by findings of (Elgendy, El-Gendy et al 2020) in their study "Public awareness in Egypt about COVID-19 spread in the early phase of the pandemic", where nearly 82% of the respondents were classified as knowledgeable about coronavirus and its treatment. Also, in the same line, (Narayana, Pradeepkumar et al 2020) in their study titled "Knowledge, perceptions, and practices towards COVID-19 pandemic among the general public of India: A cross-sectional online survey", found that the respondents' mean knowledge score of COVID-19 was 7.47, indicating that the overall accurate knowledge rate was 74.7%.…”
Section: Discussionsupporting
confidence: 74%
“…So, it is urgently advised and requested that preventive measures and quarantine should be strictly followed 23 . Also, there is an urgent requirement to have educational science and technology to fight against any such pandemic in the future 4 …”
Section: Resultsmentioning
confidence: 99%
“…The SARS‐CoV‐2 virus is mainly spread after close contact with infected people during coughing or sneezing. Moreover people may also become infected by touching a contaminated surface or object, then touching their eyes, nose or mouth 4 …”
Section: Introductionmentioning
confidence: 99%
“…14 This questionnaire was very important as the awareness and understanding of the COVID-19 instructions are very crucial to reduce morbidity and mortality, and prevent the spread of the disease. 19 The participants' awareness and practices were evaluated across all the questionnaire items. The distribution of the demographic data of the participants showed that there was a higher percentage of males, married, college graduated, a number of a family group more than three, living in cities and employees had COVID-19 disease.…”
Section: Discussionmentioning
confidence: 99%